As práticas de aprendizado organizacional nas empresas vencedoras do PGQP programa gaúcho da qualidade e produtividade - Carvalho, Mauricio Nunes Macedo de (2008)
This research aims to identify and characterize the main evolution of Management Organizations according to the Gaucho Program of Quality and Productivity, Level II - Towards Excellence, developing an examination of the main learning practices used in recognized organizations which have the Quality Award RS. This issue has an extreme importance to the award granting, which assures a good performance and maintain the survival of the business. As regards the research method, this study can be characterized as descriptive, predominantly qualitatively. Its approach was based on a study case, whose unit of analysis was considered from the universe of winner companies of the Trophy Gold Award Quality of RS. As a basis of research, the theme organizational learning in literature and its applying on Criteria for Excellence in the National Quality Awards were discussed together with the Gaucho program of Quality and Productivity. The implementation of this study has been performed through the adoption of a conceptual model for verification of organizational learning developed by Guaragna (2004). In consequence, the Report of Management was analyzed and the coordinators of the Management System of two companies, recognized by submitting processes cross outlined in a structure, were interviewed. This approach allows the occurrence of practices of organizational learning that are on course in the follow organizations: Centro Tecnológico de Mecatrônica SENAI and Medianeira Transportes Ltda. Based on the study, it is supposed that the learning can be understood as a process with specific characteristics, in which leaders have a key function in its achievement, occurring by meetings of critical analysis, preparation or revision of the Strategic Planning and benchmarking with companies in the same segment. Finally, it is suggested that further researches should be developed in order to verify the effectiveness of the practice of organizational learning and the competitive gap created to the organizations by the Quality Award RS in its different modalities.